What Determines Evaluation Outcomes? Evidence from Bi- and Multilateral Development Cooperation - Katharina Michaelowa; Axel Borrmann (Hamburg Institute of International Economics (HWWA), 2004)
Donor agencies invest considerable financial and human resources to evaluate the outcome of their development activities. To derive institutional conditions conducive to an efficient use of these resources, we develop a multi-level principal-agent model focusing on the various interests of the different actors involved in the evaluation process. The model highlights two central problems: (i) the aid agencies' conflicting objectives of transparency and self-legitimization, and (ii) the potential collusion between the evaluator and the project manager. Empirical evidence for the World Bank and different German donor agencies reveals concrete institutional requirements for a reduced evaluation bias and increased transparency.
Keywords: D73; F35; H43; 330; Development cooperation; evaluation; political economy; Entwicklungshilfe; Entwicklungsorganisation; Entwicklungsprojekt; Projektbewertung